Study of Behavioral Architectural Concepts in Kampung Susun Produktif Tumbuh Cakung, East Jakarta - Erlangga, Agus; Purwantiasning, Ari Widyati (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2023)
The development of Vertical Kampungs has begun to be seen being built and inaugurated by the government in Indonesia. Several settlements were originally horizontal Kampungs that have turned into Vertical Kampungs. The existence of this Vertical Kampung development can make it one of the suitable residential solutions for areas that are already densely populated or where land is starting to be limited. The purpose of this research is to identify the behavior of residents and understand the needs of residents in Vertical Kampungs. The method used in this study is descriptive qualitative narrative variables in the form of interviews, direct observation, and analysis of personal documents, which are illustrative, describing things as they are and the data collected is in the form of words or reasoning, pictures, and not those are the numbers. This Kampung Susun Produktif Tumbuh Cakung only meets 3 principles of the four principles of the concept of behavioral architecture according to the theory of Weinstein & David (1987).